Necrotizing fasciitis: A case report - Raedi Mahardika; Moara Gatho; Retnowati Gondo; Muhammad A. Latief (Journal of Dentomaxillofacial Science, 2021)
Objective: Necrotican fasciitis is a soft tissue infection that has a serious risk characterized by extensive tissue necrosis and gas formation in the subcutis and facial tissue areas. Infection of the facial area usually causes erythema, pain, and swelling of the skin lesions that can spread rapidly, causing numbness, and the presence of necrotic tissue for several days. Surgical debridement is a mandatory step and should be performed as soon as possible as it is the most crucial part of management of Necrotizing fasciitis. The most important determinants of mortality are the timing and adequacy of debridement. Case Report: A 48 year old female came to the emergency unit with complaints of pain and swelling in the left mandible since one week before admission to the hospital. The patient had a history of uncontrolled diabetes mellitus. The patient was diagnosed with a diagnosis of left buccal Necrotizing fasciitis and left sub-mandibular abscess extending to the submental e.c GP tooth 38 with type 2 diabetes mellitus. The patient is planned to incise and drain the abscess and debridement for necrotizing fascitis Results: After 2 months of treatment with antibiotic therapy and wound debridement of necrotizing fascitis, the wound had improved Conclusion: Succesful result in treating Necrotizing fasciitis can be achieved by thorough initial diagnosis, adequate debridement, empirical broad-spectrum antibiotic coverage, and multidiciplinary treatment from associated department.